Uji Kualitas Mikrobiologi Air Minum Isi Ulang di Kota Palopo - Suhaeni Suhaeni; Nurasia Nurasia (Universitas Cokroaminoto Palopo, 2021)
This study aims to determine the quality of refilled drinking water in the city of Palopo. This research uses descriptive method which describes the quality of refilled drinking water based on sample testing in the laboratory. Samples were taken randomly in 3 different locations, namely Binturu, Balandai and Mancani, which represent drinking water depots in the city of Palopo. The results showed that the quality of refilled drinking water was still below the standard set by the government for direct consumption.